2021
DOI: 10.1101/2021.11.23.469778
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome assembly of the JD17 soybean provides a new reference genome for Comparative genomics

Abstract: Cultivated soybean (Glycine max) is an important source for protein and oil. Many elite cultivars with different traits have been developed for different conditions. Each soybean strain has its own genetic diversity, and the availability of more high-quality soybean genomes can enhance comparative genomic analysis for identifying genetic underpinnings for its unique traits. In this study, we constructed a high-quality de novo assembly of an elite soybean cultivar Jidou 17 (JD17) with chromsome contiguity and h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Cultivars therefore tend to be less related between regions, and reference genomes of commercial varieties from different regions are needed to facilitate soybean molecular breeding. Notably, reference genomes are now available for the Japanese cultivar Enrei; the Chinese cultivars Zhonghuang 13, Jidou 17, and Tianlong 1; and the US cultivar Lee (Shimomura et al, 2015;Shen et al, 2018Shen et al, , 2019Valliyodan et al, 2019;Jia et al, 2020;Yi et al, 2022) (Table 1).…”
Section: The Progress Of Soybean Genome Studiesmentioning
confidence: 99%
“…Cultivars therefore tend to be less related between regions, and reference genomes of commercial varieties from different regions are needed to facilitate soybean molecular breeding. Notably, reference genomes are now available for the Japanese cultivar Enrei; the Chinese cultivars Zhonghuang 13, Jidou 17, and Tianlong 1; and the US cultivar Lee (Shimomura et al, 2015;Shen et al, 2018Shen et al, , 2019Valliyodan et al, 2019;Jia et al, 2020;Yi et al, 2022) (Table 1).…”
Section: The Progress Of Soybean Genome Studiesmentioning
confidence: 99%
“…Since the majority of publicly available SNP data for major crop species has yet to be updated on the recent wave of ultra-high-quality reference genomes coming online, we applied GVCW to call SNPs, with the same large resequencing datasets, on the most current and publicly available genome releases for rice (i.e., the 16 genome Rice Population Reference Panel) [20][21][22] , maize (B73 v4 and v5) 23 , sorghum (Tx2783, Tx436, and TX430) 24 , and soybean (Wm82 and JD17) 25 . The results, shown in Table 1, revealed that an average of 27.3 M (rice), 32.6 M (sorghum), 168.9 M (maize), and 16.2 M (soybean) SNPs per genome could be identified for each crop species, of which 3.0 M (rice), 7.8 M (sorghum), 4.4 M (maize), and 6.1 M (soybean) SNPs are located in exons using SNPEff 26 (Table 1 and Supplementary Table 4).…”
mentioning
confidence: 99%
“…The genome published in 2018 uses single-molecule real-time sequencing technology (PacBio RSII) to assemble the genome, which had covered 98.94% of all sequences(Xiao et al 2013;Wang et al 2019). In diploid soybean, the reference genome constructed by PacBio RSII had covered 99.65% of the whole genome sequence(Yi et al 2022).…”
mentioning
confidence: 99%